Efficacy of Controlled Memory and Shape Memory Nickel Titanium Instruments in Removing Filling Material from Severely Curved Root Canals: An Ex Vivo Study - Zevallos-Quiroz, Cesar Andre; Perez, Ivan E; Garcia-Rupaya, Carmen Rosa (Iranian Endodontic Journal, 2019)
Introduction: The aim of the present study was to compare the efficacy of four NiTi instruments with different properties (shape memory and control memory), in both rotary and reciprocating motions, during retreatment procedures. Methods and Materials: Mesial canals of thirty-two mandibular molars were instrumented, obturated, and then scanned with” Cone-beam Computed Tomography” (CBCT). Teeth were randomly divided into 4 groups (n=8) according to each system: “Shape Memory” (SM) instruments including Reciproc (R25 file) and ProTaper Next (X3 and X2 file), “Controlled Memory” (CM) instruments including WaveOne Gold (Primary file) and Hyflex (30.06 and 25.06 file). The specimens were rescanned after retreatment procedures. The volume of the residual material left inside the canals, the operating time and the fractured files were analyzed. ANOVA and student t-tests were used for statistical analysis. Results: There were no significant differences in the percentage of the residual filling material or requiring time amongst different groups of instruments (P>0.05). However, CM instruments presented the highest frequency of fractured files [2 SM instruments (12.5%) and 7 CM instruments (43.75%)] with a significant difference (P=0.023). Conclusions: This ex vivo study showed that CM and SM instruments can remove filling materials from mandibular mesial root canals during retreatment procedures; nonetheless the CM instruments had a higher frequency of fractured files. No system was able to completely remove the filling materials. Therefore, additional procedures and techniques are needed to improve root canal cleanliness. Keywords: Endodontics; Retreatment; Root Canal Preparation; Tooth Root